2013
DOI: 10.3171/2013.1.peds12475
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic findings in 2 children with cerebral paragonimiasis with hemorrhage

Abstract: Hemorrhagic events associated with cerebral paragonimiasis are not rare, especially in children and adolescents; however, angiographic evidence of cerebrovascular involvement has not been reported. The authors describe angiographic abnormalities of the cerebral arteries seen in 2 children in whom cerebral paragonimiasis was associated with hemorrhagic stroke. The patients presented with acute intracerebral and subarachnoid hemorrhage. Angiography revealed a beaded appearance and long segmental narrowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Clinical manifestations of cerebral paragonimiasis are mainly due to parasite migration, ovulation, and production of toxic substances. Intracranial hemorrhage is due to vasculitis and vasospasms [8]; therefore, if intracranial hemorrhage was caused by arteriovenous malformation, the pathological examination would show red cells and hemosiderin. Thus, in this case, the pathological examination showed diffusive clots with inflammatory cell infiltration of predominantly eosinophils, and then the main reason for intracranial hemorrhage was due to cerebral paragonimiasis rather than arteriovenous malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations of cerebral paragonimiasis are mainly due to parasite migration, ovulation, and production of toxic substances. Intracranial hemorrhage is due to vasculitis and vasospasms [8]; therefore, if intracranial hemorrhage was caused by arteriovenous malformation, the pathological examination would show red cells and hemosiderin. Thus, in this case, the pathological examination showed diffusive clots with inflammatory cell infiltration of predominantly eosinophils, and then the main reason for intracranial hemorrhage was due to cerebral paragonimiasis rather than arteriovenous malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al 6 confirmed the existence of focal cerebral vasculitis by digital subtraction angiography, but pathological evidence was lacking. The pathological analysis revealed prominent eosinophilic infiltration and granuloma formation.…”
Section: Strokementioning
confidence: 95%